2008
DOI: 10.1016/j.soildyn.2007.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of pile response to lateral spreading by 3-D soil–water coupled dynamic analysis: Shaking in the direction of ground flow

Abstract: Numerical predictions of a series of shake table tests are presented in this paper in order to examine the accuracy of a 3-D effective stress analysis in predicting the behavior of piles subjected to liquefaction-induced ground flow. For a rigorous assessment of the analysis, "Class B" predictions are reported in which numerical and constitutive model parameters were set before the event, and the target motion was used as an input motion in the analysis. Modeling of the stress-strain behavior of sand, identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…In addition to the referred experimental e orts, numerical studies have been carried out by various codes and platforms. Some notable instances of such studies include: Finn et al [11], Tabesh & Poulos [12], Miyazaki et al [13], Finn and Fujita [14], Klar et al [15], Liyanapathirana and Poulos [16,17], Chang et al [18], Bhattacharya et al [19], Elgamal et al [20], Cheng and Jeremic [21], Cubrinovski et al [22], Rahmani and Pak [23], Asgari and Oliaei [24], Sarkar et al [25], Bouckovalas and Chaloulos [26], Asadi and Shari pour [27], and Lin et al [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to the referred experimental e orts, numerical studies have been carried out by various codes and platforms. Some notable instances of such studies include: Finn et al [11], Tabesh & Poulos [12], Miyazaki et al [13], Finn and Fujita [14], Klar et al [15], Liyanapathirana and Poulos [16,17], Chang et al [18], Bhattacharya et al [19], Elgamal et al [20], Cheng and Jeremic [21], Cubrinovski et al [22], Rahmani and Pak [23], Asgari and Oliaei [24], Sarkar et al [25], Bouckovalas and Chaloulos [26], Asadi and Shari pour [27], and Lin et al [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The S-D model has been extensively verified through rigorous simulations of down-hole array records at liquefaction sites, seismic centrifuge tests, large-scale shake-table tests on pile foundations and case histories of damaged piles in the 1995 Kobe earthquake (e.g. [13] and references therein). Further details on the computation of the constitutive model parameters used in the analysis is given in Bowen and Cubrinovski [8] and Cubrinovski and Ishihara [10,11].…”
Section: Computational Modelmentioning
confidence: 99%
“…The results indicated that the maximum dynamic bending moment of pile in soft clay was about 1.5 times higher than the maximum static bending moment. Cubrinovski et al [5] studied the pile response to lateral spreading by 3-D soil-water coupled dynamic analysis by shaking in the direction of ground flow. Liyanapathirana and Poulos [9] studied the analysis of pile behavior in liquefying sloping ground.…”
Section: Introductionmentioning
confidence: 99%